Developing an ESQ-based e-learning model to improve learning outcomes and student character - Khardin, Alvien; Jalinus, Nizwardi; Arwizet; Muskhir, Mukhlidi (Universitas Jambi, Indonesia, 2025)
This research aims to improve the learning outcomes of class X students in manufacturing engineering drawing at SMK Dhuafa Padang by implementing ESQ-based e-learning model. The method used is Research and Development (R&D), which includes planning, development, trial, and product revision stages. The research results indicate that ESQ-based e-learning model effectively improve student learning outcomes. In the trial phase, 86.67% of students scored ≥ 70, showing a significant increase compared to before the implementation of this device. In addition, ESQ-based e-learning model was validated by experts and positively influenced student character, with a positive regression coefficient of 0.720. This research concludes that ESQ-based e-learning model improves student learning outcomes and character and can be used as a valid, practical, and efficient learning medium in manufacturing engineering drawing.